Diamela Eltit : reading the mother - Green, Mary (Colección Támesis. Monografías, 2007)
The textual and linguistic emphasis on the maternal body in the narrative fiction of Diamela Eltit is fundamental to understanding the critical challenge posed by her work in the Chilean context.